Study on the Influence of Different Structure Cranks on the Dynamic Balancing of Crank-group Driving Mechanism - Lu Wuhui; Cao Jujiang; Wu Yao; Liu Yansong (Jixie chuandong)
In order to study the influence of different structural forms of counterweight crank on the dynamic balance of crank-group mechanism,the dynamic balance conditions is proposed based on the mass moment substitution method and moment of momentum substitution method and the considering the application of this mechanism in tobacco packaging machine,the three virtual prototyping simulation model of six crank-group mechanism with different structural forms of crank are established. The simulation results show that fan-shaped crank,which has better dynamic balance effect than rectangular crank and triangle crank,is the best suited as the counterweight crank structure. It has important reference value and guiding significance for the design and optimization of physical prototype of crank-group mechanism in the future.